Lexis of destruction in the Russian and Serbian languages - Krstić Мaja R. (Južnoslovenski Filolog)
The semantic category of destructiveness is one of the most important components of the general semantic system, which manifests itself - either explicitly or implicitly - in a qualitative and quantitative change in the structure of an object at the macro- and/or micro level through various (direct or indirect) specific actions, processes, states or relationships with strong negative connotations. It has its own linguistic status and its own lexical base (lexis of destruction). This category and its lexical stock occupy a significant place in the general classification of lexemes of the Russian and Serbian languages. The terms “destruction” and “destructiveness” almost always refer to negative, destructive actions, processes or phenomena. The main characteristics of destruction in the broadest sense include: change, deformation, disintegration of something; structural changes under the impact of various forces (physical, mechanical, spontaneous) or humans. The result of destruction is usually the destruction of something (partial or complete). The semantic field of destructiveness contains verbs at its core, and the peripheral part consists of nouns, adjectives, adverbs and other terminological vocabulary with destructive semantics. The central unit of such a verb-centric field is the verb destroy, which forms the semantic basis of many other lexemes in this category.